Japan Society of Hepatology Guidelines for the Management of Hepatitis B Virus Infection: 2019 update (Hepatology research, 2020)
The Drafting Committee for Hepatitis Management Guidelines established by the Japan Society of Hepatology published the first version of the Guidelines for the Management of Hepatitis B in 2013 (first English version in 2014), and has since been publishing updates to the Guidelines as new drugs become available, with the latest original Japanese version being Version 3.1. Herein, the Drafting Committee publishes the second English version that contains all the changes made since the first English version of the guidelines was published in 2014. This 2019 version covers: (i) the nucleos(t)ide analogs, tenofovir disoproxil fumarate and tenofovir alafenamide; (ii) updates to treatment recommendations and management of drug‐resistant hepatitis B virus that reflect the new availability of these drugs; and (iii) new information about hepatitis B virus reactivation with each update. This latest update also contains information about treatment goals, indications for treatment and cessation of nucleos(t)ide analog therapy, most of which were covered by the first version.